An Ultra-Wideband Local Positioning System for Highly Complex Indoor Environments - Waldmann, Benjamin; Ebelt, Randolf; Vossiek, Martin; Weigel, Robert (International Conference on Localization and GNSS (ICL-GNSS) 2012, 2012)
In this paper a novel approach for a high precision local positioning radar using an ultra-wideband (UWB) technique is presented. The concept is based on the standard frequency modulated continuous wave (FMCW) radar principle combined with short pulses to fulfill the emission limits given by the official regulatory authorities. Besides the well known advantages of a FMCW radar, the proposed system implies a wide frequency bandwidth. With this concept, a high accuracy in dense multipath indoor environments can be achieved, ideally suited for 1D, 2D, and 3D localization applications for complex industrial environments. Investigations on the achievable performance of such an UWB system show very promising results and are presented within this paper. A prototype system was fabricated which operates at the center frequency of 7.5 GHz utilizing a bandwidth of 1 GHz. With the setup presented in this paper the distance between two wireless units can be measured achieving a standard deviation and absolute accuracy in the low centimeter range, even in challenging multipath environments. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEH.anultr